Analisis Kepuasan Poli Gigi Puskesmas Kabupaten Agam - Chairani Habibah; Elfindri (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This study aims to find out the satisfaction of dental clinic patients at Padang Luar Community Health Center and IV Koto Community Health Center, then compare satisfaction.. This research uses five dimensions of satisfaction, reliability, empathy, tangible, assurance and responsiveness, with comparative descriptive research, analyzing and comparing the satisfaction of dental clinic patients at the Community Health Center. In Padang Luar and IV Koto. The population of this study are patients from the two health centers. The data collecting applies questionnaires.The respondent are the patients of dental clinic. Data processing by SPSS 25. Based on linear regression, it shows that the dimensions of empathy and tangibles have a significant positive influence (<0.05), while the dimensions of reliability, assurance and responsiveness does not have a significant effect (>0.05) on patient satisfaction at the Padang Luar Health Center dental clinic. Patient satisfaction at the IV Koto Health Center dental clinic actually shows different results. The dimensions that have a significant influence (<0.05) are reliability, tangible, and assurance, while empathy and responsiveness do not have a significant influence (>0.05 ). The results of the comparison of dental clinic patient satisfaction at the two health centers using the Mann Whitney test method showed that there were no significant differences.